Uncertainties of atmospheric polarimetric measurements with sun-sky radiometers induced by errors of relative orientations of polarizers. (April 2018) - Li, Li; Li, Zhengqiang; Li, Kaitao; Sun, Bin; Wu, Yanke; Xu, Hua; Xie, Yisong; Goloub, Philippe; Wendisch, Manfred
Highlights: Errors of relative orientations of polarizers are introduced into the Mueller matrix of the Cimel polarized sun-sky radiometer. A method to quantify the errors of relative orientations of the polarizers is developed. The consistency of the results is tested. Uncertainties of the Stokes parameters, degree and angle of linear polarization induced by errors of relative orientations are studied. Abstract: In this study errors of the relative orientations of polarizers in the Cimel polarized sun-sky radiometers are measured and introduced into the Mueller matrix of the instrument. The linearly polarized light with different polarization directions from 0° to 180° (or 360°) is generated by using a rotating linear polarizer in front of an integrating sphere. Through measuring the referential linearly polarized light, the errors of relative orientations of polarizers are determined. The efficiencies of the polarizers are obtained simultaneously. By taking the error of relative orientation into consideration in the Mueller matrix, the accuracies of the calculated Stokes parameters, the degree of linear polarization, and the angle of polarization are remarkably improved. The method may also apply to other polarization instruments of similar types.